OPTIMIZATION OF LASER POWDER BED FUSION PROCESS IN INCONEL 625 TOWARDS PRODUCTIVITY - KRMASHA, MANAR NAZAR ABD (My University, 2022)
Laser Powder Bed Fusion (L-PBF) is a metal additive manufacturing technique that uses a laser beam as a heat source to melt metal powder selectively. Because of the process small layer thicknesses, laser beam diameter, and powder particle size, L-PBF allows the fabrication of novel geometries and complex internal structures with enhanced properties. However, the main disadvantages of the L-PBF process are high costs and a lengthy production time. As a result, shortening the manufacturing process while maintaining comparable properties is exceptionally beneficial. Inconel 625 (IN625) is a nickel-based superalloy becoming increasingly popular in marine, petroleum, nuclear, and aerospace applications. However, the properties of IN625 parts produced by casting or forging are challenging to control due to their low thermal conductivity, high strength and work hardening rate, and high chemical complexity. Furthermore, IN625 alloy is regarded as a difficult-to-machine material. As a result, it is worthwhile to seek new technologies to manufacture complex-shaped IN625 parts with high dimensional accuracy. IN625 alloy is known for its excellent weldability and high resistance to hot cracking; thus, IN625 alloy appears to be a promising candidate for additive manufacturing. This thesis presents an experimentally focused study on optimizing L-PBF processing parameters in IN625 superalloy to increase process productivity while maintaining high material density and hardness. This study had four stages: preliminary, exploratory, modelling, and optimization. The first stage was devoted to conducting a literature review and determining the initial processing parameters. The second stage concentrated on determining the process window, for which single tracks were printed with two high levels of laser power (300, 400 W), five levels of scan speed (500, 700, 900, 1100, 1300 mm/s), and five levels of powder layer thickness (30, 60, 90, 120, 150 µm). Then, the process window was defined after investigating the top views and cross-sections of the tracks. Stage 3 involved printing 48 cubes (10 × 10 × 10 mm^3) with a laser power of 400 W, scan speeds of (700, 900, 1100, 1300 m/s), layer thicknesses of (60, 90, 120, 150 µm), and overlap percentages of (10, 30, 50%). As a result, the density of cubes was measured, and a statistical multiple regression analysis was used to predict it. Stage 4 involved estimating four sets of ideal processing parameters (based on statistical modelling of relative density) and printing 24 cubes (10 × 10 × 10 mm^3), six samples for each set. Finally, the relative density, hardness, and productivity of the samples were assessed, and a trade-off was determined. Even with the thickest powder layer of 150 µm (highest process productivity), samples with a mean relative density greater than 99% (i.e., 99.31% by Archimedes principle and 99.82% by image analysis) were printed. These findings are consistent with previously published results for L-PBF IN625 samples manufactured with smaller layer thicknesses ranging from 20 to 40 µm while maintaining comparable material hardness. The findings of this study are noteworthy because IN625 parts can be printed with higher powder layer thicknesses (less production time) while retaining similar material properties to those published with typical layer thicknesses ranging from 20 to 40 µm. Reduced production time due to optimized processing parameters can lead to significant energy and cost savings.
Keywords: Additive Manufacturing; Laser Powder Bed Fusion; Inconel 625; Process Optimization; Powder Layer Thickness; Density; Hardness; Productivity